White gold dry granules, white gold dry granule glaze, marble ceramic tile and preparation method of marble ceramic tile
By adopting the new formula of the raw material of Wujin dry grains, the black copper iron crystals are formed, which solves the problem of single decorative effect of the existing Wujin glaze, and achieves the effect of forming a colorful luster on the glaze surface, and improves the antibacterial performance.
Patent Information
- Application Number
- CN202510410548.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing black gold glaze has a single decorative effect and lacks a rich colorful gloss effect, which limits the diversity of its decorative applications.
A new raw material formula for black gold dry particles is adopted, including sodium feldspar, sodium carbonate, zinc oxide, brown corundum, boric acid, limonite, spherical soil, fluorite, quartz, dolomite and copper oxide. It is used to form 60-200 mesh dry particles through high-temperature melting and low-temperature water quenching to form 60-200 mesh dry particles, and black copper iron crystals are formed on the glaze surface to achieve a colorful gloss effect.
The black gold decorative effect of forming a colorful luster on the glaze surface is achieved, which enhances the diversity and stability of the decorative effect, and at the same time improves the antibacterial properties of the glaze surface.
Smart Images

Figure CN119912165A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to black gold dry particles, black gold dry particle glaze, marble tiles and preparation methods thereof. Background Art
[0002] Traditional Jingdezhen Wujin glaze is mainly made of Wujin clay with an iron content of 13.4%. This Wujin clay not only has a very high content of iron oxide, but also contains coloring elements such as manganese and diamond. It is usually fired at a high temperature of 1300-1330℃ and in a heat-reducing atmosphere. The decorative effect of the existing Wujin glaze mainly presents a single luster at different angles, and the decorative effect of Wujin glaze can still be enriched. Summary of the invention
[0003] The main purpose of the present invention is to provide a black gold dry particle. After the raw material components are prepared, the formed crystals can form a black gold decorative effect with colorful luster on the glaze surface, adding new decorative effects to the development of black gold glaze.
[0004] To achieve the above purpose, the present invention provides a black gold dry particle, which includes the following raw materials, by weight percentage: albite: 8-10%, sodium carbonate: 5-10%, zinc oxide: 5-15%, brown corundum: 1-6%, boric acid: 3-6%, limonite: 10-15%, ball clay: 5-10%, fluorite: 7-10%, quartz: 14-18%, dolomite: 4-8% and copper oxide: 1-2%.
[0005] The above-mentioned black gold dry granules are melted, cooled, crushed and sieved to form black gold dry granules. The feldspar, quartz and brown corundum (usually stable at high temperatures above 2000°C) in the formula react with limonite and copper oxide to form black copper iron crystals under the action of the low eutectic mixture. The crystals can form a colorful luster on the glaze surface. They not only have a dense structure, high stability, and are not easy to change color, but also have low porosity and few pore defects. Incorporating zinc oxide into the black copper iron crystals not only helps to reduce the melting point of the black gold dry granules, but also forms effective antibacterial ions attached to the surface of the dry granules, which is beneficial to improve the antibacterial effect of the glaze.
[0006] The invention provides a black gold dry particle, which is applied to glaze and obtains a black gold decorative effect with colorful luster on the glaze surface after firing, thereby enriching the decorative effects of existing black gold glaze and marble tiles.
[0007] Preferably, the weight percentage of the zinc oxide is 10-15%. Within this preferred range, a balance between cost and antibacterial effect is achieved, and the antibacterial effect is better.
[0008] Preferably, the copper oxide is a 180-325 mesh copper oxide powder, which is wrapped on the surface of particles obtained by mixing, melting, water quenching and crushing the other raw materials, and the particle size of the particles is 60-200 mesh. Generally speaking, the particles obtained by water quenching and crushing are first wrapped with a binder, and then mixed and wrapped with copper oxide powder. Compared with the dry particles obtained after conventional melting, cooling, crushing and screening, the preparation step of melting, heat preservation, cooling and crushing into dry particles and then wrapping on the dry particles is easier to fuse and wrap, and the resulting decorative effect is more obvious.
[0009] In a specific embodiment, the preparation method of Wujin dry granules comprises the following steps: (1) According to the raw material ratio of Wujin dry granules, other raw materials except copper oxide are melted at a high temperature of 1450-1550°C, kept warm for 3-5 hours, quenched with water below 5°C, crushed and sieved to form 60-200 mesh dry granules; (2) Add 10-30% methylcellulose water to the dry particles and stir for 1-2 hours, then coat with copper oxide powder; (3) Drying at 200-230 degrees Celsius to form the black gold dry particles that are evenly bonded with the copper oxide powder.
[0010] Compared with the dry particles obtained after conventional melting, cooling, crushing and screening, after the melting, heat preservation, cooling and crushing into dry particles in the preparation step, methylcellulose water is first added for stirring, then rolled to bond the copper oxide powder and then dried to form black gold dry particles with uniformly bonded copper oxide powder. If the cooling temperature is higher than this range, uneven cooling is likely to occur, and the transparency of the obtained particles is not high.
[0011] The present invention provides a black gold dry granule glaze, the raw material of which is the black gold dry granule described in the above scheme. The black gold dry granule glaze is applied to tiles or other ceramic products, and after firing, a black gold decorative effect with a seven-color luster formed on the glaze surface can be obtained.
[0012] Preferably, the dry material components of the black gold dry particle glaze include the following raw materials by weight percentage: Lithium porcelain stone: 10-25%, zinc oxide: 10-15%, the black gold dry particles: 16-22%, limestone: 5-7%, fluorite: 11-16%, barium carbonate: 2-7%, potassium feldspar: 12-17%, ball clay: 6-9% and strontium carbonate: 12-17%.
[0013] The above composition of the dry material ingredients of the Wujin dry granule glaze is conducive to reducing the firing temperature range, and in the subsequent firing step, the firing can be carried out in an oxidizing atmosphere, breaking through the limitations of the traditional Wujin glaze on the firing atmosphere (reducing atmosphere) and the firing temperature range (1300-1330°C).
[0014] The present invention also provides a method for preparing marble tiles, comprising the following preparation steps: S1: using ceramic blank raw materials to make a green body, drying and standby; S2: applying glaze; S3: Screen printing or roller rolling the black gold dry granular glaze described in any of the above schemes according to a preset pattern; S4: Firing.
[0015] The marble tiles prepared by this solution have the corresponding beneficial effects of the aforementioned solutions, which will not be described in detail here.
[0016] Preferably, the black gold dry granular glaze comprises dry material components and glaze-forming auxiliary materials, and the weight ratio of the dry material components to the glaze-forming auxiliary materials is 1:1; The dry material ingredients, by weight percentage, include the following raw materials: Lithium porcelain stone: 10-25%, zinc oxide: 10-15%, the black gold dry particles: 16-22%, limestone: 5-7%, fluorite: 11-16%, barium carbonate: 2-7%, potassium feldspar: 12-17%, ball clay: 6-9% and strontium carbonate: 12-17%; The glaze auxiliary materials include, by weight percentage, printing paste: 60-70%, printing oil: 15-25% and water: 15-20%.
[0017] Usually, the proportion of printing paste and printing oil in glaze auxiliary materials is 1:4~6, and the ratio of dry ingredients to water is 1:0.5~0.8. However, the present technical solution adopts a lower amount of water and a large proportion of printing paste, which may easily affect the quality of the glaze and may cause agglomeration in conventional glazes. However, after the glaze auxiliary materials of the present solution are mixed with the dry material components, the obtained black gold dry particle glaze slurry has better dispersibility, is not easy to agglomerate, and maintains better glaze quality after firing.
[0018] Further preferably, the present invention provides a method for preparing marble tiles, wherein the glaze in step S2 is a black gold glaze, which comprises the following raw materials by weight percentage: Lithium feldspar: 28-50%, kaolin: 10-15%, quartz: 5-10%, wollastonite: 5-10%, burnt kaolin: 5-10%, zinc oxide: 1-2%, barium carbonate: 5-10% and zirconium silicate: 10-15%, In step S4, the firing temperature is 1170-1190° C., and the firing time is 55-65 min. The combination of the aforementioned black gold glaze and black gold dry particle glaze is conducive to firing by a medium-temperature fast firing method in an oxidizing atmosphere.
[0019] Preferably, there is a step of forming a pattern layer by inkjet after step S2.
[0020] Preferably, after step S1, the green body dried in step S1 is moistened with water so that the surface of the green body contains 5-8% moisture. To further ensure the decorative effect, if the moisture content of the green body surface is too high or too low, it is not conducive to the glaze to effectively adhere to the green body surface, thereby affecting the black gold decorative effect of the glaze surface.
[0021] The present invention provides a marble tile, which is prepared by the method for preparing a marble tile described in any of the above schemes, thereby having the beneficial effects of the above schemes, which will not be described in detail here.
[0022] Compared with the prior art, the present invention provides a black gold dry particle which is applied to the glaze and forms a black gold decorative effect with a colorful luster on the glaze surface after firing, thereby enriching the decorative effects of the existing black gold glaze and marble tiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 This is a glaze texture image magnified 100 times in the screen printing embodiment of the marble tile of the present invention; Figure 2 The present invention provides a black gold decorative effect diagram of the colorful gloss of the marble tile glaze surface.
[0025] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0027] The following is an example of a method for preparing marble tiles to illustrate the technical solution of the present invention. In the following examples and comparative examples, raw materials, reagents, etc. without special instructions are all commercially available, and the same batch of raw materials or reagents are used in the examples and comparative examples; the preparation methods without special conditions are all prepared by conventional, well-known preparation methods.
[0028] Example 1 The specific example in Example 1 refers to this preparation method, comprising the following steps: S1. The green body is pressed using conventional ceramic green body raw materials, dried and set aside; S2. The green body after drying in step S1 is moistened with water so that the surface of the green body contains 5-8% moisture; S3. The conventional transparent glaze after ball milling is evenly applied to the body obtained in step S2 and set aside; S4. Prepare the materials according to the weight percentage of each raw material of the black gold dry glaze, mix them thoroughly and then perform ball milling, screen print the glaze layer according to the preset pattern, and apply the ball-milled black gold marble dry glaze mixture evenly through the large screen device to the body obtained in step S3 for standby use; The Wujin dry granular glaze is mixed with the glaze auxiliary materials, and ball-milled for 26 minutes per 100g. The obtained Wujin dry granular glaze mixture is sieved through a 325-mesh screen for standby use; Specifically, the Wujin dry granules include the following raw materials by weight percentage: Sodium feldspar: 10%, sodium carbonate: 9%, zinc oxide: 11%, brown corundum: 5%, boric acid: 6%, limonite: 15%, ball clay: 10%, fluorite: 10%, quartz: 18%, dolomite: 4%, copper oxide: 2%. All raw materials are melted at high temperature of 1500℃, quenched in low temperature water to form a molten block, and crushed and sieved to obtain 60~200 mesh black gold dry particles.
[0029] S5. The green body obtained in step S4 is calcined in a kiln at high temperature and then polished to obtain black gold marble dry granular glaze marble tiles. In specific embodiments 1-1 to 1-3, the firing is carried out in an oxidizing atmosphere at a firing temperature of 1200-1220°C and a firing time of 65-80 minutes. When the firing temperature is higher, the corresponding firing time is shortened, and the technicians can adjust it accordingly.
[0030] Among them, the black gold dry granule glaze composition in the specific embodiment of Example 1 is as follows: Example 1-1 The black gold dry granular glaze comprises dry material components and glaze-forming auxiliary materials, and the weight ratio of the dry material components to the glaze-forming auxiliary materials is 1:1.
[0031] The dry material composition, in terms of weight percentage, includes the following raw materials: lithium porcelain stone: 25%, zinc oxide: 10%, black gold dry particles: 16%, limestone: 5%, fluorite: 11%, barium carbonate: 3%, potassium feldspar: 12%, ball clay: 6% and strontium carbonate: 12%.
[0032] The glaze auxiliary materials, calculated by weight percentage, include: printing paste: 60%, printing oil: 20% and water: 20%.
[0033] Example 1-2 The black gold dry granular glaze comprises dry material components and glaze-forming auxiliary materials, and the weight ratio of the dry material components to the glaze-forming auxiliary materials is 1:1.
[0034] The dry material composition, calculated by weight percentage, includes the following raw materials: lithium porcelain stone: 20%, zinc oxide: 10%, black gold dry particles: 17%, limestone: 5%, fluorite: 12%, barium carbonate: 5%, potassium feldspar: 12%, ball clay: 6% and strontium carbonate: 13%.
[0035] The glaze auxiliary materials, measured by weight percentage, include: printing paste: 70%, printing oil: 15% and water: 15%.
[0036] Examples 1-3 The black gold dry granular glaze comprises dry material components and glaze-forming auxiliary materials, and the weight ratio of the dry material components to the glaze-forming auxiliary materials is 1:1.
[0037] The dry material composition, in terms of weight percentage, includes the following raw materials: lithium porcelain stone: 18%, zinc oxide: 11%, black gold dry particles: 18%, limestone: 5%, fluorite: 13%, barium carbonate: 4%, potassium feldspar: 12%, ball clay: 6% and strontium carbonate: 13%.
[0038] The glaze auxiliary materials, calculated by weight percentage, include: printing paste: 66%, printing oil: 15% and water: 19%.
[0039] Comparative Example 1 The specific preparation method of the marble tile is roughly the same as that of Example 1-2, except that no limonite is added to the raw material components of the black gold dry particles, and other raw material components are adaptively adjusted in proportion.
[0040] The performance test items of the specific embodiments and the specific comparative examples were tested, and the corresponding effects are shown in the following table: Table 1 Performance test project description: The decorative effect is obtained by technicians observing the glaze decorative effect from different angles at close range under sufficient light conditions; Antibacterial effect: Apply roughly equal initial amounts of Escherichia coli and Staphylococcus aureus to the surface of the tested marble tile, test the residual amount of Escherichia coli and Staphylococcus aureus after 168 hours, record the initial amount of bacteria and the residual amount of bacteria, and calculate the sterilization rate. The formula for calculating the sterilization rate is: (initial amount - residual amount) / initial amount * 100%.
[0041] The quality of the glaze is obtained by technicians observing the glaze at close range under sufficient light conditions. When no pores can be observed with the naked eye, the glaze quality is good; when individual pores can be observed with the naked eye, the glaze quality is average; when a large number of pores can be observed clustered together with the naked eye, the glaze quality is poor.
[0042] Dispersion effect: During the preparation process, technicians observed the dispersion effect of the Wujin dry granule glaze and the degree of agglomeration: good dispersion with no agglomeration; general dispersion with a little agglomeration; poor dispersion with obvious agglomeration.
[0043] It can be seen from the above data that Examples 1-1 to 1-3 use the black gold dry granular glaze of the present application to prepare marble tiles, which helps to form a black gold decorative effect with a colorful luster on the glaze surface of the marble tiles.
[0044] In Comparative Example 1, no limonite was added and no black copper-iron crystals were formed. A black gold decorative effect with a single luster at different angles was formed on the glaze surface, which was consistent with the effect of traditional black gold glaze.
[0045] Example 2 The specific preparation method is roughly the same as that of Example 1-2, except that: the glaze auxiliary materials, calculated by weight percentage, include: printing paste: 20%, printing oil: 40% and water: 40%.
[0046] Example 3 The specific preparation method of marble tiles is roughly based on Example 1-2, except that the preparation method of black gold dry particles is: (1) According to the raw material ratio of Wujin dry particles, the raw materials except copper oxide are melted at a high temperature of 1500°C, kept warm for 4 hours, and then quenched in water at a low temperature of 3°C, crushed and sieved to form 60-200 mesh dry particles; (2) After the dry particles are mixed with 180-325 mesh copper oxide powder, 20% by weight of solute methylcellulose water is added and stirred for 1.5 hours; (3) Drying at 200 degrees Celsius to form black gold dry particles that are evenly bonded with copper oxide powder.
[0047] Example 4 The specific preparation method of the marble tile is roughly based on Example 1-2, with the difference being that the surface glaze uses black gold glaze.
[0048] The black gold glaze includes the following raw materials, by weight percentage: lithium feldspar: 45%, kaolin: 10%, quartz: 10%, wollastonite: 5%, burnt kaolin: 5%, zinc oxide: 1%, barium carbonate: 9% and zirconium silicate: 14%, methyl cellulose: 0.25% and sodium tripolyphosphate: 0.75%.
[0049] After mixing the dry materials of the black gold glaze, add 38% water by weight of the black gold glaze and ball mill for 18 minutes per 100g. The obtained black gold glaze mixture is sieved through a 325-mesh screen for standby use.
[0050] Specifically, in step S5, the high temperature calcination temperature is 1190°C, the calcination time is 60 minutes, and the atmosphere is oxidizing.
[0051] Example 5 The specific preparation method of the marble tiles is roughly the same as that of Example 1-2, except that: as shown in the following table, the specific content of zinc oxide in the black gold dry particles is adjusted, and the composition of other raw materials is adaptively adjusted in proportion.
[0052] Table 2 The performance test items of the specific embodiments and the specific comparative examples were tested, and the corresponding effects were shown as follows: Table 3 It can be seen from the above data that the glaze auxiliary materials in Example 2 are adjusted to a conventional ratio relative to Example 1-2, and the obtained black gold dry particle glaze mixture glaze slurry generally has a little agglomeration in dispersion performance, and the glaze surface quality is general, that is, the dispersion effect and the glaze surface quality are deteriorated. It can be seen from the effect data of Example 2 and Examples 1-1 to 1-3 that when the glaze auxiliary materials are adjusted to the preferred ratio, that is, the weight ratio of the dry material components of the black gold dry particle glaze and the glaze auxiliary materials is 1:1, and the glaze auxiliary materials are measured by weight percentage, including printing paste: 60-70%, printing oil: 15-25% and water: 15-20%, the obtained black gold dry particle glaze mixture glaze slurry has better performance, is well dispersed without agglomeration, and the glaze surface quality after firing is better.
[0053] In Example 3, the preparation method of black gold dry particles is adjusted compared with that in Example 1-2, and the resulting marble tiles have a better melting state, better wrapping performance, and a better black gold decorative effect with a colorful luster.
[0054] Compared with Examples 1-2, Example 4 prefers black gold glaze as the glaze. By combining the black gold glaze and the black gold dry particle glaze, the firing time and firing range are further shortened. Through similar experiments, it is found that when the raw materials of the black gold glaze, by mass percentage, include: lithium feldspar: 28-50%, kaolin: 10-15%, quartz: 5-10%, wollastonite: 5-10%, burned kaolin: 5-10%, zinc oxide: 1-2%, barium carbonate: 5-10% and zirconium silicate: 10-15%, when it is combined with the black gold dry particle glaze of the present application, the firing temperature can be further reduced to 1170~1190℃, and the firing time can be further reduced to 55~65min.
[0055] Example 5 The specific content of zinc oxide in the Wujin dry particles is adjusted relative to Example 1-2. When the zinc oxide content is lower than 10wt%, the antibacterial performance is not significantly improved, and the sterilization rate of Escherichia coli and Staphylococcus aureus is only about 70%; when the zinc oxide content is higher than 15wt%, the antibacterial performance decreases instead of increasing, and a better comprehensive effect cannot be obtained. Only when the content of zinc oxide in the Wujin dry particles is 10-15wt%, the glaze of the obtained marble tile achieves a balance between antibacterial effect and cost, and the sterilization rate reaches more than 95%, so it has a better comprehensive effect.
[0056] In summary, the black gold dry granules are prepared by using the black gold dry granule raw material of the present application. The feldspar, quartz and brown corundum in the formula react with limonite and copper oxide to form black copper iron crystals under the action of the low eutectic mixture, and the crystals show a colorful luster at different angles on the glaze. Incorporating zinc oxide into the black copper iron crystals not only helps to reduce the melting point of the black gold dry granules, but also forms effective antibacterial ions attached to the surface of the dry granules, which is beneficial to improve the antibacterial effect of the glaze, and can be fired in an oxidizing atmosphere, which also reduces the firing temperature relative to the prior art. As shown in the example of comparative example 1, when limonite is not added, the black gold dry granule raw material fails to form black copper iron crystals, and a black gold decorative effect showing a colorful luster is not obtained on the glaze. When the zinc oxide in the black gold dry granules is preferably 10~15wt%, the antibacterial effect of the marble tile glaze can be further improved. The combination of black gold dry granular glaze and black gold surface glaze can further reduce the firing temperature to 1170~1190℃, and the firing time to 55~65min, thus achieving medium-temperature fast firing.
[0057] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. Wujin dry granules, characterized in that, The invention comprises the following raw materials by weight percentage: albite: 8-10%, sodium carbonate: 5-10%, zinc oxide: 5-15%, brown corundum: 1-6%, boric acid: 3-6%, limonite: 10-15%, ball clay: 5-10%, fluorite: 7-10%, quartz: 14-18%, dolomite: 4-8% and copper oxide: 1-2%.
2. The black gold dry granules as claimed in claim 1, characterized in that The weight percentage of the zinc oxide is 10-15%.
3. The Wujin dry granules as claimed in claim 1 or 2, characterized in that The copper oxide is 180-325 mesh copper oxide powder, which is coated on the surface of particles obtained by mixing, melting, water quenching and crushing the other raw materials, and the particle size of the particles is 60-200 mesh.
4. Black gold dry granular glaze, characterized in that: The raw material is the black gold dry granules as described in any one of claims 1 to 3.
5. The black gold dry granular glaze according to claim 4, characterized in that: The dry material components of the black gold dry granular glaze include the following raw materials in terms of weight percentage: Lithium porcelain stone: 10-25%, zinc oxide: 10-15%, the black gold dry particles: 16-22%, limestone: 5-7%, fluorite: 11-16%, barium carbonate: 2-7%, potassium feldspar: 12-17%, ball clay: 6-9% and strontium carbonate: 12-17%.
6. A method for preparing marble tiles, characterized in that: The method comprises the following preparation steps: S1: using ceramic blank raw materials to make a green body, drying and standby; S2: applying glaze; S3: Screen printing or roller rolling the black gold dry granular glaze as claimed in claim 4 or 5 according to a preset pattern; S4: Firing.
7. The method for preparing marble tiles according to claim 6, characterized in that: The black gold dry granular glaze comprises dry material components and glaze-forming auxiliary materials, and the weight ratio of the dry material components to the glaze-forming auxiliary materials is 1:1; The dry material ingredients, by weight percentage, include the following raw materials: Lithium porcelain stone: 10-25%, zinc oxide: 10-15%, the black gold dry particles: 16-22%, limestone: 5-7%, fluorite: 11-16%, barium carbonate: 2-7%, potassium feldspar: 12-17%, ball clay: 6-9% and strontium carbonate: 12-17%; The glaze auxiliary materials include, by weight percentage, printing paste: 60-70%, printing oil: 15-25% and water: 15-20%.
8. The method for preparing marble tiles according to claim 6 or 7, characterized in that: The glaze in step S2 is a black gold glaze, which comprises the following raw materials by weight percentage: Lithium feldspar: 28-50%, kaolin: 10-15%, quartz: 5-10%, wollastonite: 5-10%, burnt kaolin: 5-10%, zinc oxide: 1-2%, barium carbonate: 5-10% and zirconium silicate: 10-15%; In step S4, the firing temperature is 1170-1190° C., the firing time is 55-65 min, and the atmosphere is oxidizing.
9. Marble tiles, characterized in that, The marble tile is prepared by the method for preparing the marble tile according to any one of claims 6 to 8.
Citation Information
Patent Citations
Micro-nano composite glaze material
CN105036558A
Golden black glaze for jun-porcelain and preparation method of golden black glaze
CN109095771A
Colorful dry frit particles and ceramic tile decorated by colored dry frit particles
CN115466056A
Frit, preparation method of frit, glaze, ceramic tile and preparation method of ceramic tile
CN118930049A
Cited By
Positioning metal dry particle and preparation method thereof
CN121005520A